Manifestation of agronomically valuable traits in the progeny of a sorghum mutant carrying the genetic construct for RNA silencing of the γ-kafirin gene - L. A. Elkonin; N. V. Borisenko; T. E. Pylaev; O. A. Kenzhegulov; S. Kh. Sarsenova; N. Yu. Selivanov; V. M. Panin (Вавиловский журнал генетики и селекции)
Improving the nutritional value of grain sorghum, a drought- and heat-tolerant grain crop, is an important task in the context of global warming. One of the reasons for the low nutritional value of sorghum grain is the resistance of its storage proteins (kafirins) to proteolytic digestion, which is due, among other things, to the structural organization of protein bodies, in which γ-kafirin, the most resistant to proteases, is located on the periphery, encapsulating more easily digested α-kafirins. The introduction of genetic constructs capable of inducing RNA silencing of the γ-kafirin (gKAF1) gene opens up prospects for solving this problem. Using Agrobacterium-mediated genetic transformation of immature embryos of the grain sorghum cv. Avans we have obtained a mutant with improved digestibility of endosperm proteins (up to 92 %) carrying a genetic construct for RNA silencing of the gKAF1 gene. The goal of this work was to study the stability of inheritance of the introduced genetic construct in T2–T4 generations, to identify the number of its copies, as well as to trace the manifestation of agronomically valuable traits in the offspring of the mutant. The mutant lines were grown in experimental plots in three randomized blocks. The studied lines were characterized by improved digestibility of kafirins, a modified type of endosperm, completely or partially devoid of the vitreous layer, an increased percentage of lysine (by 75 %), reduced plant height, peduncle length, 1000-grains weight, and grain yield from the panicle. In T2, a line with monogenic control of GA resistance was selected. qPCR analysis showed that in different T3 and T4 plants, the genetic construct was present in 2–4 copies. In T3, a line with a high digestibility of endosperm proteins (81 %) and a minimal decrease in agronomically valuable traits (by 5–7 %) was selected.